2005
DOI: 10.1111/j.1439-0396.2005.00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of xylanase and phospholipase to wheat‐based diets for weaner pigs

Abstract: The effects of supplementing a wheat-based diet for weaner pigs with exogenous xylanase and phospholipase on ileal and faecal nutrient digestibilities and on the level of microbial metabolites in ileal digesta were examined. Fourteen piglets, weaned at 11 days, were fitted with a simple T-cannula at the distal ileum. The pigs were offered a control diet or diets supplemented with xylanase and phospholipase individually or in combination, in a two period crossover design. The combination of xylanase and phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
3
13
0
1
Order By: Relevance
“…40 Thus, it can be concluded from the results of the present study that SIDs of CP and AAs in newly weaned pigs are relatively independent of the age of the animals provided that the daily feed intake in relation to BW remains relatively constant during the duration of the experiment. Notably, according to some reports, 24,41,42 AIDs of CP and AA may decline at the conclusion of the experiment, which is in agreement with the results reported herein for SIDs. Potential experimental or dietary factors which may be responsible for the decrease in ileal digestibilities still need to be elucidated.…”
Section: Effect Of Period On Standardised Ileal Digestibilities Of Crsupporting
confidence: 93%
“…40 Thus, it can be concluded from the results of the present study that SIDs of CP and AAs in newly weaned pigs are relatively independent of the age of the animals provided that the daily feed intake in relation to BW remains relatively constant during the duration of the experiment. Notably, according to some reports, 24,41,42 AIDs of CP and AA may decline at the conclusion of the experiment, which is in agreement with the results reported herein for SIDs. Potential experimental or dietary factors which may be responsible for the decrease in ileal digestibilities still need to be elucidated.…”
Section: Effect Of Period On Standardised Ileal Digestibilities Of Crsupporting
confidence: 93%
“…The BW of the animals was determined at the beginning of each of the three experimental periods to maintain a constant feed intake level in relation to the piglets' BW. The level of feed intake may affect AID and IAAL B in piglets (Moter and Stein, 2004;Diebold et al, 2005). In piglets, weaned at 21 days of age or earlier, the voluntary daily feed intake, on the basis of BW, often does not exceed 35 g/kg BW in the first week after weaning (Brooks and Tsourgiannis, 2003).…”
Section: Animals and Housingmentioning
confidence: 99%
“…However, Li et al (1993) reported in early weaned pigs a significant increase in ileal AA digestibilities with age and proposed that piglets may have a limited capacity for CP digestion and AA absorption. In addition, factors such as body weight (BW) and age (Caine et al, 1997a and1997b), and the level of feed intake (Moter and Stein, 2004;Diebold et al, 2005) may affect AID and IAAL B in piglets. Thus, SID of CP and AA may differ considerably between piglets and growerfinisher pigs.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of xylanase into the rye-or wheat-based diets of broiler chickens resulted in an improvement in weight gain of chicks and their feed conversion efficiency (Bedford and Classen, 1992). Similar improvements can be obtained for pigs fed on a wheat-based diet supplemented with xylanases and phospholipases (Diebold et al, 2005).…”
Section: Applications Of Xylanasessupporting
confidence: 64%